The Application of Three-dimensional Shear Wave Elastography in the Detection of Inguinal Lymph Node Metastasis in Gynecological Malignancies - Yuping Shen; Jiulong Dai; Jiami Li; Man Lu (Clinical and Experimental Obstetrics & Gynecology)
Background: Accurate assessment of lymph node involvement is essential for prognosis and guiding treatment decisions in gynecological cancers, as it directly influences therapeutic strategies and patient outcomes. However, conventional imaging techniques, such as ultrasound and computed tomography (CT), demonstrate limited accuracy in determining the nature of lymph nodes. This study implements three-dimensional shear wave elastography (3D-SWE), an innovative technique that quantifies the stiffness of inguinal lymph nodes (ILN) in patients with gynecological cancers. This approach offers a more comprehensive assessment of ultrasound elastography compared to traditional methods. Methods: This retrospective study evaluated 120 ILNs from patients with gynecological cancers who underwent conventional ultrasound (US), two-dimensional shear wave elastography (2D-SWE), and multiplanar 3D-SWE. The diagnostic performance was analyzed using receiver operating characteristic (ROC) methodology, enabling a comprehensive comparison of the sensitivity and specificity of 3D-SWE relative to conventional ultrasound and 2D-SWE. Pathology results from lymph node resections or biopsies served as the reference standard. Results: Final pathology confirmed 65 metastatic and 55 benign lymph nodes. The maximum (Emax) and average (Emean) elasticity values from 2D-SWE and 3D-SWE for malignant lymph nodes were significantly higher than those for benign lymph nodes (p < 0.0001). ROC analysis indicated that for identifying metastatic lymph nodes, the area under the curve (AUC) values were 0.798 for 2D-SWE Emax, and 0.828, 0.839, and 0.816 for the transverse, sagittal, and coronal planes of 3D-SWE Emax, respectively. The differences between these AUC values were not statistically significant (p > 0.05). Furthermore, Emax values consistently surpassed Emean values in terms of characterization accuracy across modalities. Although no significant differences were observed between 2D-SWE and 3D-SWE, the sagittal view Emax yielded the best AUC, indicating optimal diagnostic precision overall. Conclusions: 3D-SWE, particularly using the sagittal Emax parameter, effectively distinguishes benign lymph nodes from metastatic ones by quantitatively evaluating the stiffness of ILNs in relation to gynecological tumors. Serving as a dependable diagnostic method for lymph nodes, 3D-SWE may help reduce the necessity for invasive biopsy procedures in some cases.